Factors Affecting Geographic Variation in Echolocation Calls of the Endemic Myotis davidii in China. (16th August 2013) - Jiang, Tinglei; You, Yuyan; Liu, Sen; Lu, Guanjun; Wang, Lei; Wu, Hui; Berquist, Sean; Ho, Jennifer; Puechmaille, Sébastien J.; Feng, Jiang
Abstract: The sensory drive hypothesis of speciation predicts that divergence in communication systems will occur when environments differ and that this sensory divergence can ultimately promote speciation. The factors affecting geographic evolution in acoustic signals remain poorly understood, especially in the contexts of high gene flow. This study investigated variation patterns in peak frequency emitted by the Chinese endemic Myotis davidii on a broad geographic scale by evaluating the relative importance of morphological, environmental, geographic, and genetic variables. Significant variation in peak frequency was observed among regions, but peak frequencies among populations within region had some percentage of similarity. Differences in peak frequency were not associated with morphological difference, genetic structure, and geographic distance among regions, which suggested that peak frequency divergences in M. davidii were not the primary driver of regions' isolation in a context of weak gene flow. Within the Middle East Plain (MEP), one of the regions delineated in this study, peak frequency differences of M. davidii were not significantly correlated with genetic distance and geographic distance among populations, suggesting that peak frequency was not be subject to cultural drift within MEP. Our results provide evidence that geographic variation in echolocation call design may evolve as a consequence of local adaptation to climate conditions.